Pengembangan Aplikasi Mobile Manajemen Tugas dan Produktivitas dengan Integrasi Fitur Kalender dan Reminder - Zakarias, Riza Abid; Ikrimach (Jurnal Informatika Ekonomi Bisnis, 2025)
This study aims to develop a mobile-based task and productivity management application integrated with calendar and reminder features. The objective is to help users organize, monitor, and complete tasks efficiently while maintaining optimal productivity. The research adopts a system development approach consisting of several stages, namely analysis, design, implementation, and evaluation. The main features of the developed application include task scheduling, automatic reminders, and an interactive calendar display to assist users in managing deadlines and daily activities. Based on the results of the evaluation, the application successfully delivers reminder notifications according to the specified schedule and provides a structured view of tasks within the calendar interface. The findings indicate that the integration of task management, reminder, and calendar features can improve users’ time management and task completion efficiency.